ENTREPRENEURIAL RECOGNITION: A REVIEW AND BIBLIOMETRIC ANALYSIS - Nurruddin Zanky, Mokhammad; Rahma, Adelia; Wahyu Ariyanto, Muhammad (Universitas Negeri Surabaya, 2025)
Phenomenon/Issue: Entrepreneurial recognition is a pivotal but underexplored concept in entrepreneurship studies, particularly in understanding how individuals identify and act upon business opportunities. The current literature lacks conceptual clarity and systematic mapping of this domain. Purpose: This study aims to conduct a comprehensive bibliometric analysis to map the landscape of entrepreneurial recognition research and identify key themes, gaps, and directions for future inquiry. Novelty: Unlike prior studies that focus narrowly on opportunity recognition, this paper provides the first systematic bibliometric overview of “entrepreneurial recognition” using co-word analysis to uncover structural relationships between key concepts and trends. Research Methods: A total of 198 publications from 2011 to 2021 were retrieved using the Publish or Perish software from Google Scholar. After applying selection criteria, 97 articles were analyzed using VOSviewer to conduct co-word mapping, and performance and science mapping approaches as suggested by Zupic & Čater (2015). Results: The findings reveal that scholarly discussions around entrepreneurial recognition remain in early development, with core themes including opportunity identification, entrepreneurial alertness, and the role of human and social capital. The visualization outputs identify five research clusters and highlight a need for further exploration into conceptual clarity, theoretical diversity, and the role of entrepreneurial alertness. Research Contributions: This study contributes to the entrepreneurship literature by providing a visual and thematic synthesis of entrepreneurial recognition research. It offers a foundation for scholars to refine theoretical frameworks, broaden methodological approaches, and investigate under-researched constructs such as entrepreneurial alertness and its impact on opportunity identification